2016
DOI: 10.1152/jn.00852.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor-mediated responses in medial vestibular and prepositus hypoglossi nuclei neurons showing distinct neurotransmitter phenotypes

Abstract: Cholinergic transmission in both the medial vestibular nucleus (MVN) and prepositus hypoglossi nucleus (PHN) plays an important role in horizontal eye movements. We previously demonstrated that the current responses mediated via nicotinic acetylcholine receptors (nAChRs) were larger than those mediated via muscarinic acetylcholine receptors (mAChRs) in cholinergic MVN and PHN neurons that project to the cerebellum. In this study, to clarify the predominant nAChR responses and the expression patterns of nAChRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 59 publications
3
16
1
Order By: Relevance
“…In addition, two double transgenic rats were used for histologic observation of inhibitory and cholinergic neurons in the INC and PHN. The double transgenic rats were generated by crossing the choline acetyltransferase (ChAT)-tdTomato and VGAT-Venus transgenic rats ( Saito et al, 2015 ; Zhang et al, 2016 ). These rats (21 PND) were transcardially perfused with 0.05 M phosphate buffer (PB, pH 7.4), followed by 4% paraformaldehyde in PB under deep anesthesia induced via isoflurane inhalation (vaporized with oxygen) followed by intraperitoneal injection of sodium pentobarbital (>50 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, two double transgenic rats were used for histologic observation of inhibitory and cholinergic neurons in the INC and PHN. The double transgenic rats were generated by crossing the choline acetyltransferase (ChAT)-tdTomato and VGAT-Venus transgenic rats ( Saito et al, 2015 ; Zhang et al, 2016 ). These rats (21 PND) were transcardially perfused with 0.05 M phosphate buffer (PB, pH 7.4), followed by 4% paraformaldehyde in PB under deep anesthesia induced via isoflurane inhalation (vaporized with oxygen) followed by intraperitoneal injection of sodium pentobarbital (>50 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for slice preparation and whole cell patch‐clamp recordings were similar to those previously described (Zhang, Kaneko, Yanagawa, & Saito, ; Zhang, Yanagawa, & Saito, ). Briefly, rats [18–21 postnatal days (PND)] were deeply anesthetized with isoflurane and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of nAChRs has been demonstrated in the prepositus hypoglossi nucleus (PHN) (Clarke et al 1985;Schwartz 1986;Zaninetti et al 1999), which is a brainstem center involved in gaze control (Büttner and Büttner-Ennever 2006;Fukushima et al 1992;McCrea and Horn 2006;Moschovakis 1997). In fact, the PHN receives cholinergic input from the pedunculopontine tegmental nucleus and the laterodorsal tegmental nucleus (Higo et al 1990;Iwasaki et al 1999;McCrea and Horn 2006), and our previous studies demonstrated the expression of functional nAChRs in PHN neurons (Zhang et al 2014(Zhang et al , 2016. Local application of acetylcholine (ACh) to recorded neurons induced three types of current responses that were characterized on the basis of their different rise and decay times: current responses showing a fast rise and a fast decay (F type), current responses showing a slow rise and a slow decay (S type), and current responses showing a fast rise and a slow decay (FS type).…”
Section: Introductionmentioning
confidence: 91%
“…Because it is usually difficult to produce an experimental system to clarify this issue thoroughly, the data on the relationships between the current types that were mediated via different nAChR subtypes and the neuronal properties that were previously determined must be accumulated step by step to elucidate their participations. In our previous study, we clarified the current types of glutamatergic, inhibitory (GABAergic and/or glycinergic), and cholinergic neurons using transgenic rats (Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%